2021
DOI: 10.20853/35-2-3904
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the success rates of students with no prior accounting knowledge in obtaining a professional accounting degree

Abstract: Several South African universities do not require students to have completed Accounting at secondary school level in order to enrol for a degree in Accounting. At Stellenbosch University such students with no prior Accounting knowledge can still graduate and receive a Bachelor of Accounting degree (which is the first step of many towards becoming a CA (SA)) within the minimum time frame of three years given that an Accounting conversion examination is passed at the beginning of their second academic year. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Accounting conversion students were successful in obtaining their professional degree in Accounting within the minimum time of three years and 81% of these students eventually obtained their professional degree in Accounting (up until the date of the study), irrespective of how long it took. Rossouw and Brink's (2020) finding suggests that Accounting as a subject at secondary school is not necessarily essential to obtain a professional degree in Accounting.…”
Section: Literature Reviewmentioning
confidence: 96%
See 4 more Smart Citations
“…Accounting conversion students were successful in obtaining their professional degree in Accounting within the minimum time of three years and 81% of these students eventually obtained their professional degree in Accounting (up until the date of the study), irrespective of how long it took. Rossouw and Brink's (2020) finding suggests that Accounting as a subject at secondary school is not necessarily essential to obtain a professional degree in Accounting.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Accounting conversion students en route to becoming a CA(SA). The pearl growing or snowballing search strategy, together with Rossouw and Brink (2020) found that 50% of the first-year B. Accounting conversion students were successful in obtaining their professional degree in Accounting within the minimum time of three years and 81% of these students eventually obtained their professional degree in Accounting (up until the date of the study), irrespective of how long it took.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations